Toxicity Factors of Magnetite Nanoparticles and Methods of Their Research - Vazhnichaya, Elena; Semaka, Oleksandr; Lutsenko, Ruslan; Bobrova, Nellia; Kurapov, Yurii (Innovative Biosystems and Bioengineering, 2024)
Among nanoparticles (NPs) of metal oxides, magnetite NPs are the most well-known. The need for regulations related to the safety of magnetite NPs requires a deep understanding of their toxicological paradigm. The purpose of the presented review is to analyze the methods of studying the magnetite NPs toxicity and to summarize their toxicity factors based on the literature data. Literature sources were searched in the PubMed database, and 99 works were selected, supplemented with articles from other databases in some cases. It is shown that the study of the magnetite NPs toxicity became widespread during the last decade, reflecting the expansion of the list of synthesized magnetic NPs and the awareness that the prospects for their use depend on the safety of the created nanomaterial. The safety assessment of magnetite NPs on cell lines is the most popular. Primitive and more highly organized animals can be used to evaluate various aspects of the magnetite NPs toxicity. The toxicity factors of magnetite NPs depend on their characteristics (core composition, coating, size, and shape) and the mode of application (concentration, dose, exposure, type of cells, or animal model). One of the main mechanisms of nanomagnetite toxicity is the interference with iron metabolism and increased generation of reactive oxygen species leading to the disruption of cell proliferation, viability, and metabolism. Thus, the toxicity of magnetite NPs is studied by various methods and at different levels of living systems. Understanding the mechanisms of nanotoxicity should contribute to the targeted design of safe magnetic NPs.